2020
DOI: 10.1194/jlr.ra119000509
|View full text |Cite
|
Sign up to set email alerts
|

HDL inhibits endoplasmic reticulum stress-induced apoptosis of pancreatic β-cells in vitro by activation of Smoothened

Abstract: Loss of pancreatic β-cell mass and function as a result of sustained endoplasmic reticulum (ER) stress is a core step in the pathogenesis of diabetes mellitus type 2. The complex control of β-cells and insulin production involves hedgehog signaling pathways as well as cholesterol-mediated effects. In fact, data from studies in humans and animal models suggest that HDL protects against the development of diabetes through inhibition of ER stress and β-cell apoptosis. We investigated the mechanism by which HDL in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 73 publications
(47 reference statements)
0
24
0
Order By: Relevance
“…The molecular mechanisms underlying the potential beneficial functions of HDLs in β-cells are largely unknown. Intriguingly, however, a recent study found that a potential protective effect of HDL to reverse endoplasmic stress and β-cell death may involve a complex cascade of the transport, generation, and mobilization of oxysterols for the activation of the hedgehog signaling receptor Smoothened [ 124 ].…”
Section: Diabetesmentioning
confidence: 99%
“…The molecular mechanisms underlying the potential beneficial functions of HDLs in β-cells are largely unknown. Intriguingly, however, a recent study found that a potential protective effect of HDL to reverse endoplasmic stress and β-cell death may involve a complex cascade of the transport, generation, and mobilization of oxysterols for the activation of the hedgehog signaling receptor Smoothened [ 124 ].…”
Section: Diabetesmentioning
confidence: 99%
“…Local expression of ApoC-III within the pancreatic islets has led to β-cell failure in mice [ 53 ]. In contrast, it was found that high-density lipoprotein (HDL) expression in β-cell had a protective role against ER stress [ 102 ].…”
Section: The Link Between Lipoprotein Export and β-Cell Dysfunctiomentioning
confidence: 99%
“…By contrast, high-density lipoprotein (HDL) [ 5 , 6 , 7 , 8 ], its major apolipoprotein (apo), apoA-I [ 7 , 9 , 10 , 11 ], and/or the ATP binding cassette (ABC) transporters with which they interact [ 12 , 13 , 14 , 15 , 16 ], can provide protection to beta cells and pancreatic islets in experimental models, findings generally supported by clinical data [ 17 , 18 , 19 , 20 , 21 ]. Studies variously link these protective functions with sterol removal or efflux from beta cells [ 8 , 12 , 13 , 14 , 15 , 16 ]; others report cholesterol- and/or transporter-independent effects of apoA-I and HDL [ 7 , 10 ], while conflicting reports exist regarding beta cell function in carriers of loss of function (LOF) mutations in ABCA1 [ 22 , 23 ]. Some of these divergent outcomes may be attributed to the heterogeneous nature of HDL and its cargo molecules [ 24 , 25 ], and to the widely differing concentrations of apoA-I (10 μg protein mL −1 to 900 μg mL −1 ) and/or HDL (50 μg protein mL −1 to 1 mg mL −1 ) used, or required, to demonstrate the protective effect of this lipoprotein in human and rodent beta cell models (reviewed in [ 5 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, numerous cell signalling pathways are altered in beta cells by exposure to apoA-I and HDL, including G protein coupled receptor (GPCR) activation of adenyl cyclase, protein kinase A and forkhead box protein 01 (Fox01) [ 9 ], calcium signalling [ 7 ], and activation of hedgehog (Hh) receptor Smoothened (SMO) [ 8 ], protein kinase B [ 26 ] and sphingosine-1-phosphate receptors (S1PR1-3) [ 5 , 24 , 27 ]. Transcription factors, such as the Liver X receptor (LXR), peroxisome proliferator activator receptor alpha (PPARα), FOXO1 and BTB domain and CNC homolog 1 (BACH1) have also emerged as key factors orchestrating cellular responses to fatty acids such as palmitate [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation